Posteromedial Buttress Plate for Schatzker 6 Fractures as Double Column Fixation - Usman Zafar Dar, Ali Muqaddas, Mohammad Nauman Shahid, Muhammad Ahmed, Sameer Ahmed, Naeem Hussain, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Treatment of Schatzker Type 6 fractures is to use a posteromedial buttress plate as part of a double-column fixation technique. Materials & Methods: The design of this study was a cross sectional study design and this study was conducted in DHQ Teaching Hospital Gujranwala. patients with posterior medial fracture of Schatzker type 6 and having associated damage of some soft tissue present within the joint underwent surgery at our institutional operation theatre. In this Study setting we included total 20 patients (14 male [70%] and 6 females [30%]) who came with Bicondylar fractures having Comminuted Posteromedial Fragments of tibia. Results: Of the Patients, 12 (60%) had excellent results, 5(25%) had good results , and 3 (15%) had fair results. In total, 17 patients (85%) achieved cheering results. Walking, Stability, and motion were good or excellent in all cases. Practical Implication: One of the main advantages of the posteromedial buttress plate fixation technique is that it provides support to the medial column of the tibia, which is an important weight-bearing structure in the lower extremity. By restoring the structural integrity of the medial column, the technique can help promote early weight-bearing and facilitate early rehabilitation. All displaced posteromedial tibial plateau fractures should be surgically stabilized and buttressed using plate to restore joint congruity and prevent late subluxation and early arthritis. The aim is to study the role of posteromedial plating in the management of complex tibial plateau fractures with a posteromedial fragment Conclusion: Use of a posteromedial buttress plate as part of a double-column fixation technique can be an effective approach for treating Schatzker Type 6 fractures. Keywords: Fixation of Posterior Column, Buttress plate, Schatzker 6 fracture